New lamps for old: financialised governance of cities and clean energy. Issue 4 (4th July 2019) - Webb, Janette
ABSTRACT: Using a six-year case study of Glasgow's Sustainable City business model, this paper examines interactions between financialised governance of cities and clean energy strategies. Research on the role of cities in developing clean energy has paid limited attention to the interaction with financialised governance of infrastructure, which makes the implementation of plans largely dependent on private investment. A conceptual approach combining economic sociology of actor networks and urban political economy is used to analyse the career of the business model designed to transform old infrastructures into new clean energy assets. The analysis focuses on interactions between city council, public bodies and electricity distribution network business. Climate policies are creating uncertainties for energy businesses over revenues from ageing networks, suggesting scope for alliance with local governments. Making new liquid assets for clean energy from old infrastructure is however shown to be a process marked by instability and reversals. In conclusion, it is argued that concepts from actor-network theory and urban political economy used together reveal the hidden contingencies of financialisation in particular socio-technical interactions, and their materiality in the context of climate change.